Analytical PSpice model for SiC MOSFET based high power modules. (July 2016) - Johannesson, Daniel; Nawaz, Muhammad
Abstract: A simple analytical PSpice model has been developed and verified for a 4H–SiC based MOSFET power module with voltage and current ratings of 1200 V and 120 A. The analytical simulation model is a temperature dependent silicon carbide (SiC) MOSFET model that covers static and dynamic behavior, leakage current and breakdown voltage characteristics. The technology dependent MOSFET modeling parameters are extracted from characterization measurements, datasheets and PSpice simulations at various temperatures. The SiC MOSFET model is implemented in the PSpice circuit simulation platform using PSpice standard components and analog behavior modeling (ABM) blocks. The MOSFET switching performance is investigated under influence of different circuit elements, such as stray inductance, gate resistance and temperature, in order to study and estimate on-state and switching losses pre-requisite for design of various converter and inverter topologies. The performance of the SiC MOSFET model is fairly accurate and correlates well with the measured results over a wide temperature range.